The Capacity of the Smithies Model to Explain the Growth Trend by Endogenous Forces - Kromphardt, Jurgen; Dorfner, Joachim (Econometrica, 1974)
[The introduction of ratchet effects into the consumption and investment functions of the Smithies model does not provide an endogenous explanation of cyclical fluctuations and growth, contrary to Smithies' expectation. As in other cycle models, the growth trend can only be explained by exogenous forces.]